25‐OH‐vitamin D, parathyroid hormone, and calcium serum levels in captive common marmosets (Callithrix jacchus): Reference values and effect of age, sex, season, and closure of long bone epiphyses. Issue 3 (15th February 2018) - Bosseler, Leslie; Bakker, Jaco; Duchateau, Luc; Remarque, Ed; Langermans, Jan A.M.; Cornillie, Pieter; Chiers, Koen
Abstract: Background: To date, reference values for 25‐OH‐vitamin D, parathyroid hormone (PTH), and calcium in serum of common marmosets ( Callithrix jacchus ) based on a large sample size are not available. Methods: Serum reference values for these parameters were determined and correlated with sex, age, season of sampling, and time of long bone epiphyseal closure in captive‐housed marmosets. Results and Conclusions: The 90% reference range for serum 25‐OH‐vitamin D is 47.40‐370.4 nmol/L, for PTH 2.10‐30.51 pmol/L, and for calcium 2.08‐2.63 mmol/L. Lower levels of vitamin D were measured in fall compared with the other seasons. Levels of PTH were higher in males than in females, and calcium levels were lower in younger animals compared with older marmosets. No other effects of age, sex, season, or timing of growth plate closure were found.